2003
DOI: 10.1242/jcs.00208
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPase Tc10 and its homologue RhoT induce N-WASP-mediated long process formation and neurite outgrowth

Abstract: Rho family small GTPases regulate multiple cellular functions through reorganization of the actin cytoskeleton. Among them, Cdc42 and Tc10 induce filopodia or peripheral processes in cultured cells. We have identified a member of the family, designated as RhoT, which is closely related to Tc10. Tc10 was highly expressed in muscular tissues and brain and remarkably induced during differentiation of C2 skeletal muscle cells and neuronal differentiation of PC12 and N1E-115 cells. On the other hand, RhoT was predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 72 publications
2
102
1
Order By: Relevance
“…Inhibition of TC10 activity by expression of a dominant-negative mutant in tail muscle cells of Ciona intestinalis larva impairs myofibril assembly. Consistent with our results in ascidia, TC10 mRNA is easily detected in striated muscle tissues from mouse and human (Abe et al, 2003;Neudauer et al, 1998). In the mouse C2C12 cell line, TC10 mRNA is detected at a moderate level in undifferentiated myoblasts.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Inhibition of TC10 activity by expression of a dominant-negative mutant in tail muscle cells of Ciona intestinalis larva impairs myofibril assembly. Consistent with our results in ascidia, TC10 mRNA is easily detected in striated muscle tissues from mouse and human (Abe et al, 2003;Neudauer et al, 1998). In the mouse C2C12 cell line, TC10 mRNA is detected at a moderate level in undifferentiated myoblasts.…”
Section: Introductionsupporting
confidence: 91%
“…In the mouse C2C12 cell line, TC10 mRNA is detected at a moderate level in undifferentiated myoblasts. It is then induced in myotubes and reaches high levels in terminally differentiated myotubes (Abe et al, 2003). Although JeBailey and co-workers observed TC10 mRNA transcripts in differentiated rat L6 skeletal muscle cells and 3T3-L1 adipocytes, the protein was only detected in adipocytes (JeBailey et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Aspenstrom et al (59) showed that overexpression of constitutive active forms of the GTPases Wrch, RhoD, and Rif induced thin filopodia in porcine aortic endothelial cells, whereas overexpression of active L61Cdc42 instead induced lamellipodia. Moreover, the GTPase TC10, which is a member of the Cdc42 family, has also been shown to induce filopodia in cells (60). Interestingly, TC10 has been shown to be activated downstream of Crk in response to insulin or osmotic shock (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this defect was not fully penetrant. It is likely that the lack of Cdc42 can be partially compensated by other highly related GTPases, such as TC10 (Tanabe et al, 2000) or TCL/RhoT (Vignal et al, 2000;Abe et al, 2003). However, Cdc42 is clearly required for the efficient establishment of polarity and growth of the axon.…”
Section: Cdc42 Ablation Disrupts Neuronal Polarizationmentioning
confidence: 99%